2010
DOI: 10.1590/s0100-69162010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem computacional do fluxo unidimensional de água em meio não saturado do solo

Abstract: O estudo do fluxo de água em zonas não saturadas do solo é de grande importância para pesquisas relacionadas à disponibilidade hídrica para o desenvolvimento das plantas. Devido ao alto custo, ao tempo demandado e ao esforço humano nas investigações de campo, os modelos matemáticos, aliados às técnicas numéricas e avanços computacionais, constituem-se em uma ferramenta importante na previsão desses estudos. No presente trabalho, objetivou-se solucionar a equação diferencial parcial não linear de Richards media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“…To validate the proposed method, we compared our numerical results with the models reported in the literature by Celia et al (1990) The present model infiltration profiles and those reported by Wendland and Pizarro (2010) are shown in Figure 2. It was observed that they accurately match since curves overlap.…”
Section: Parameters and Validationmentioning
confidence: 98%
See 3 more Smart Citations
“…To validate the proposed method, we compared our numerical results with the models reported in the literature by Celia et al (1990) The present model infiltration profiles and those reported by Wendland and Pizarro (2010) are shown in Figure 2. It was observed that they accurately match since curves overlap.…”
Section: Parameters and Validationmentioning
confidence: 98%
“…These outcomes indicate that the model presented here was a suitable approximation. Wendland and Pizarro (2010).…”
Section: Parameters and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…A distribuição da umidade no solo é o movimento da água infiltrada na zona não saturada do solo, impulsionada por entradas de água via infiltração superficial, como chuva, degelo, irrigação, e fluxos causados pela evaporação e retirada de água pelas raízes (LAIO et al, 2001;WENDLAND;PIZARRO, 2010;KANZARI;MARIEM, 2017;ZHU et al, 2018). Geralmente, o modelo usado para dinâmica de água no solo é descrito pela equação de Richards (RICHARDS, 1931), a qual combina a lei de Darcy estendida a solos insaturados com conservação de massa, como visto em (PHILIPP, 1969;HILSS et al, 1989;CE-LIA et al, 1990).…”
unclassified